Ampliação e ressignificação do ensino técnico da língua inglesa no ensino médio por meio da plataforma Moodle - RIBEIRO, Karine Campos (2020)
This dissertation aims to analyze the pedagogical potential of the Moodle Platform for Technical Teaching of the English Language. To this end, the development of the study here presented is based on tasks and activities aimed at expanding the possibilities of a Virtual Learning Environment (VLE) in face-to-face classes. These activities served to reinforce the knowledge of graduating students of the Technical courses in Foreign Trade and Logistics at the Federal Institute of Education, Science and Technology of Amapá - Santana Campus. The specific objectives of this research were outlined to describe, organize, explore, and verify the tools of the VLE that could assist the teaching of the English Language through the resources available within this virtual space. With approaches to a case study, this research followed the paths of qualitative research, and concerning data analysis, it was developed from the descriptive method. Among the instruments for data collection in this study include a pre-test, field diary, observation, questionnaire, and post-test. The analysis and discussion of the data indicate that the expansion and reframing of the technical teaching of the English language through the VLE Moodle were quite satisfactory. When using the task-based approach, students made some teaching proposals that, among other actions, combined classroom teaching with practices in virtual space, providing students with greater autonomy, motivation, and learning. The study's findings also revealed that the activities associated with the linguistic development of an additional language through some Virtual Environments contribute to the use of the language in real situations. Therefore, it allows apprentices to communicate with a greater degree of naturalness, since, from this proposal, language is no longer a foreign element, thus becoming part of the students' lives. Finally, there was a need for further research on this topic, which involves an additional language, technology, and professional technical education.